Effectiveness of diode laser and fluoride on dentin hypersensitivity treatment: A randomized single-blinded clinical trial - Pantuzzo, Érika Soares (J Indian Soc Periodontol, 2020)
BACKGROUND: This randomized single-blinded clinical trial aimed to evaluate the effectiveness of diode laser and fluoride in the treatment of dentin hypersensitivity (DH) due to gingival recession. MATERIALS AND METHODS: Twenty-eight individuals randomly distributed across three groups participated: 10 individuals who were treated with diode laser, nine who were treated with fluoride, and nine who received placebo. Pain was assessed with the Visual analog scale (VAS). Evaporative stimulus and tactile stimulus were evaluated with the verbal rating scale (VRS). VAS was applied shortly after, 6 h after, 12 h after, and 24 h after the single-session treatment for DH, whereas VRS was applied shortly after, 15 min and 7 days after the treatment. Participants' quality of life was assessed with the validated Brazilian version of the Dentine Hypersensitivity Experience Questionnaire assessing functional limitations, coping behaviors, emotional, and social impacts caused by DH. Descriptive statistics and the ANOVA test were used. Values of P < 0.05 were statistically significant. RESULTS: Diode laser significantly reduced the DH to the evaporative stimulus (P = 0.002). The application of fluoride did not change the degree of DH to evaporative and tactile stimuli (P > 0.05). The group of individuals who were treated with diode laser presented a higher reduction in DH (25.4%) when compared to the group of individuals treated with fluoride (17.1%), and the group of individuals among whom placebo had been used (2.9%). Descriptive analysis indicated that the items measuring the emotional and social impacts of DH were those with a more negative impact on the individuals. CONCLUSION: Therapy with diode laser was more effective in reducing DH than therapy with fluoride.